Implementasi Sistem Bagi Hasil dan Perlakuan Akuntansi Pembiayaan Mudharabah Studi Kasus KSPPS Muamalah Berkah Sejahtera Surabaya - Retno Wijayanti; Hendra Dwi Prasetyo (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Economic development that uses sharia principles has overgrown. This research aims to identify the procedures for mudharabah financing and profit-sharing through mudharabah contracts at KSPPS Muamalah Berkah Sejahtera Surabaya based on PSAK No. 105. In conducting research at KSPPS Muamalah Berkah Sejahtera Surabaya. The data analysis used was descriptive qualitative analysis. The study results stated that the Muamalah Berkah Sejahtera Financing Savings and Loan Cooperative had implemented the financing process well. KSPPS Muamalah Berkah Sejahtera Surabaya has shown relatively good performance in recognizing, presenting, and presenting financial statements following PSAK No. 105 when conducting mudharabah financing activities.